Effects of stockperson attitudes and handling on finishing pig behaviour and mental state - Lundin, Martina (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
This study is part of an ongoing project, PigTraWel (2019) which aims to investigate interactions between animal transporters and slaughter pigs during loading and unloading by mapping different driving methods, their effects on pigs and transporters and the efficiency of the work. Pigs are exposed to a number of environmental stressors prior to slaughter that can affect pig behaviour and welfare, the working situation of stockpeople involved and cause meat quality problems. Previous studies propose that the nature of the on-farm interactions between stockpersons and pigs may have an influence on pigs behavioural response during pre-slaughter treatments. Negative human-animal interactions on-farm are related with a high fear response in pigs, while positive human-animal interactions have been found to reduce animals fear response, increase ease of handling, and thus have benefits for both health and production. Pigs are able to generalize aversive or rewarding treatment by one stockperson and associate the treatment with the presence of humans. The aim of this study was to examine stockpersons working routines during handling of pigs in Swedish commercial pig farms and how specific stockperson handling affect pig behaviour. The study also aimed to examine stockpersons normative attitudes towards pig and pig caretaking in relation to pigs behavioural response. Previous research has found that there is a relationship between stockperson attitude and behaviour and pigs behavioural response. On-farm recordings were carried out at nine commercial pig farms at different locations in Sweden and data were collected by four different methods: a stockperson questionnaire of beliefs and perceptions, observations of working routines of stockpersons, Qualitative Behaviour Assessment of pigs and assessment of pig reactions to a human stranger. The results shows that the stockpersons included in the study performed more rough than gentle handling actions towards the pigs. However, the results could not demonstrate a significant relationship between either positive or negative human-animal interactions and pig behaviours indicative of fear or a positive emotional state. Nor was a relationship between stockperson beliefs and pig behaviour supported by the results, but the stockpersons had in general positive normative beliefs towards pigs and pig caretaking. Nevertheless, the results indicate that pigs may become less fearful in contact with human strangers the more time the stockperson spends with the pigs.